Analysis of the Effect of Economic Growth, Urbanization, Energy Consumption on CO2 Emissions in G-20 Countries for the Period 1990 – 2020 - Izmi Dwi Maharani Poetri; Taufiq Taufiq; Abdul Bashir; Anna Yulianita (UNIVED Press, 2023)
This study aims to analyze how economic growth, urbanization, energy consumption influenced to CO2 Emissions in Countries that are members of the G-20. In this study using time-series data for the period 1990 – 2020; the data utilized are sourced from World Bank database and BP Statistic. The methode uses a quantitative approach that applies the STIRPAT methode with the fixed effect methode panel data regression. The results of the study state that economic growth with GDP per capita has a positive and significant effect, meanwhile GDP per capita squared has a negative and significant on CO2 Emissions. So that it can prove the EKC hypothesis with an inverted U-Curve relationship between economic growth and CO2 Emissions. Urbanization and Energy Consumption has a positive and significant effect on CO2 Emissions.